Optimization of Spray Drying Process Parameters for the Preparation of Inhalable Mannitol-Based Microparticles Using a Box-Behnken Experimental Design - Karas, Jakub; Pavloková, Sylvie; Hořavová, Hana; Gajdziok, Jan (Pharmaceutics, 2023)
Inhalation is used for local therapy of the lungs and as an alternative route for systemic drug delivery. Modern powder inhalation systems try to target the required site of action/absorption in the respiratory tract. Large porous particles (LPPs) with a size >5 μm and a low mass density (usually measured as bulk or tapped) of <0.4 g/cm3 can avoid protective lung mechanisms. Their suitable aerodynamic properties make them perspective formulations for deep lung deposition. This experiment studied the effect of spray-drying process parameters on LPP properties. An experimental design of twelve experiments with a central point was realized using the Box-Behnken method. Three process parameters (drying temperature, pump speed, and air speed) were combined on three levels. Particles were formed from a D-mannitol solution, representing a perspective material for lung microparticles. The microparticles were characterized in terms of physical size (laser diffraction), aerodynamic diameter (aerodynamic particle sizer), morphology (SEM), and densities. The novelty and main goal of this research were to describe how the complex parameters of the spray-drying process affect the properties of mannitol LPPs. New findings can provide valuable data to other researchers, leading to the easy tuning of the properties of spray-dried particles by changing the process setup.